Contrasting land uses in Mediterranean agro-silvo-pastoral systems generated patchy diversity patterns of vascular plants and below-ground microorganisms. - Bagella, Simonetta; Filigheddu, Rossella; Caria, Maria Carmela; Girlanda, Mariangela; Roggero, Pier Paolo (Comptes rendus biologies, 2014)
The aims of this paper were (i) to define how contrasting land uses affected plant biodiversity in Mediterranean agro-silvo-pastoral-systems across a gradient of disturbance regimes: cork oak forests, secondary grasslands, hay crops, grass covered vineyards, tilled vineyards; (ii) to determine whether these patterns mirrored those of below-ground microorganisms and whether the components of γ-diversity followed a similar model. The disturbance regimes affected plant assemblage composition. Species richness decreased with increasing land use intensity, the Shannon index showed the highest values in grasslands and hay crops. Plant assemblage composition patterns mirrored those of Basidiomycota and Ascomycota. Richness in Basidiomycota, denitrifying bacteria and microbial biomass showed the same trend as that observed for vascular plant richness. The Shannon index pattern of below-ground microorganisms was different from that of plants. The plant γ-diversity component model weakly mirrored those of Ascomycota. Patchy diversity patterns suggest that the maintenance of contrasting land uses associated with different productions typical of agro-silvo-pastoral-systems can guarantee the conservation of biodiversity.
The following values have no corresponding Zotero field: publisher: Academie des sciences accession-num: 25433564
Keywords: Cork oak forests; Grass covered vineyards; Grazing; Hay crops; Secondary grasslands; Tilled vineyards

Short-term effects on sheep pastureland due to grazing abandonment in a Western Mediterranean island ecosystem: A multidisciplinary approach - Farris, Emmanuele; Filigheddu, Rossella; Deiana, Pietrino; Farris, Giovanni a; Garau, Giovanni (Journal for Nature Conservation, 2010)
Changes of pasture communities consequent to management practices resulting from land abandonment considerably affect the structure and function of the ecosystem. This study analyses the consequences of grazing abandonment in terms of plant and soil microbial diversity and fertility, on a Mediterranean upland sheep pasture, over a short period (ﬁve years). Grazing was experimentally excluded by fencing ten 10 10 m permanent plots within an area that had supported grazing until 2000, by 0.23 sheep ha 1 . Plant and soil microbial communities and physicochemical parameters were monitored within the fenced and unfenced control plots, during three sampling times from 2000 (before the fencing) to 2005. Grazing cessation notably altered the ﬂoral composition, with an average dissimilarity of 96.7% between the vegetation communities, over ﬁve years. No signiﬁcant change occurred in the control plots that were grazed throughout the sampling period. This work highlighted that, over a short term, the structural change in the speciﬁc plant composition affected only the grass species, conﬁrming that grazing favours the small-sized species over the annual species. Further, it was evident that species groups of conservational and phytogeographic interest, like the endemic and Mediterranean-Atlantic species, tended to disappear with pasture abandonment and were substituted by more widespread species throughout the Mediterranean or even the world. Pasture abandonment was accompanied by an increase of soil pH and a decrease in soil organic matter and soil nitrogen. The microbial parameters recorded at three different sampling times revealed a substantial effect of the plant community, or the time of grazing abandonment, on soil microbial abundance and diversity. Considerable importance is given to the consequences of pasture abandonment on the conservation of plant and microbial diversity and on soil fertility.
The following values have no corresponding Zotero field: publisher: Elsevier
Keywords: animal-plant interactions; Habitat directive; Land-use change; Mediterranean basin; Microbial community; plant diversity; Poetea bulbosae; Soil fertility